Are three points for a win really better than two? Theoretical and empirical evidence for German soccer - Alexander Dilger; Hannah Geyer (Westfälische Wilhelms-Universität Münster, Institut für Ökonomische Bildung (IÖB), 2008)
The effects of the three-point rule in first league German soccer are tested empirically and compared to games from the German cup-competition. The inclusion of cup games ensures that changes in league games can be attributed to the three-point rule. As a result of their relative devaluation, the number of draws should decrease. Furthermore, an increase in the number of close wins is expected. The strategy of a leading team becomes more defensive, resulting in fewer goal shootings by that team, as well as fewer shooting opportunities for the opponent. Empirical evidence supporting these effects is found.
Keywords: C72; C93; L83; 330; Fußballsport; Nichtkooperatives Spiel; Regulierung; Bewertung; Theorie; Deutschland